Design of security scheme to prevent DNS cache poisoning attacks - Chong, Zhan Ming (2019)
The Domain Name Server (DNS) plays a very important role in the internet today. DNS is a protocol that translates domain names that are human readable into numerical Internet Protocol (IP) addresses which are computer readable. DNS efficiently runs all internet applications such as internet surfing, emailing, multimedia applications and many more. However, DNS has a lack of security upgrade which led to its vulnerability by being exploited. DNS cache poisoning is an attack where attackers can forcefully introduce fake DNS information to the cache memory of domain name resolvers, users that communicate with this domain name resolvers would be directed to a wrong destination and confidential information might be stolen for financial gain or malicious intent. This is the real threat that users face today. This report studies DNS cache poisoning attacks and methods to reduce the attack.